European health examination surveys - a tool for collecting objective information about the health of the population - Tolonen, Hanna; Koponen, Päivikki; Al-Kerwi, Ala'a; Capkova, Nada; Giampaoli, Simona; Mindell, Jennifer; Paalanen, Laura; Ruiz-Castell, Maria; Trichopoulou, Antonia; Kuulasmaa, Kari; EHES Network (Archives of public health, 2018)
BACKGROUND: Representative and reliable data on health and health determinants of the population and population sub-groups are needed for evidence-informed policy making; planning and evaluation of prevention programmes; and research. Health examination surveys (HESs) including questionnaires, objective health measurements and analysis of biological samples, provide information on many health indicators that are available not at all or less reliably or completely through administrative registers or health interview surveys. METHODS: Standardized cross-sectional HESs were already conducted in the 1980's and 1990's, in the framework of the WHO MONICA Project. The methodology was developed and finally, in 2010-2012, a European Health Examination Survey (EHES) Pilot Project was conducted. During this pilot phase, an EHES Coordinating Centre (EHES CC, formerly EHES Reference Centre) was established. Standardized protocols, guidelines and quality control procedures were prepared and tested in 12 countries which conducted pilot surveys, demonstrating the feasibility of standardized HES data collection in the European Union (EU).Currently, the EHES CC operates at the National Institute for Health and Welfare (THL), Finland. Its activities include maintaining and developing the standardized protocols, guidelines and training programme; maintaining the EHES network; providing professional support for countries planning and organizing their national HESs; external quality assessment for surveys organized in the EU Member States; and development of a centralized database and joint reporting system for HES data. RESULTS: An increasing number of EU Member States are conducting national HESs, demonstrating a strong need for such surveys as part of the national health monitoring systems. Standardization of the data collection is essential to ensure that HES data are comparable across countries and over time. The work of the EHES CC helps to ensure the quality and comparability of HES data across the EU. CONCLUSIONS: HES data have been used for health monitoring and identifying public health problems; to develop health and prevention programmes; to support health policies and preparation of health-related legislation and regulations; and to develop clinical treatment guidelines and population reference values. HESs have also been utilized to prepare health measurement tools and diagnostic methods; in training and research and to increase health awareness among population.
Keywords: Comparable; Survey; Population; Representative; Health information